15 K liquid hydrogen thermal Energy Storage Unit for future ESA science missions. Issue 1 (November 2015) - de Sousa, P Borges; Martins, D; Tomás, G; Barreto, J; Noite, J; Linder, M; Fruchart, D; de Rango, P; Haettel, R; Catarino, I; Bonfait, G
Abstract: A thermal Energy Storage Unit (ESU) using liquid hydrogen has been developed as a solution for absorbing the heat peaks released by the recycling phase of a 300 mK cooler that is a part of the cryogenic chain of one of ESA's new satellites for science missions. This device is capable of storing 400 J of thermal energy between 15 and 16 K by taking advantage of the liquid-to-vapor latent heat of hydrogen in a closed system. This paper describes some results obtained with the development model of the ESU under different configurations and using two types of hydrogen storage: a large expansion volume for ground testing and a much more compact unit, suitable for space applications and that can comply with ESA's mass budget.